Green Waqf Berbasis Smart Agriculture: Rekonstruksi Instrumen Wakaf Produktif untuk Mendukung Modernisasi Pertanian Berkelanjutan - Andini Asmarini (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Waqf, as one of the instruments of Islamic social finance, has significant potential to support sustainable economic development through the productive management of endowed assets. However, the utilization of productive waqf across various development sectors remains suboptimal, particularly in promoting innovation and technology-driven transformation. Meanwhile, the implementation of smart agriculture offers promising solutions to enhance agricultural productivity and efficiency but continues to face financing constraints, especially among smallholder farmers. This study aims to analyze the reconstruction of Green Waqf based on Smart Agriculture from the perspective of Sharia Economic Law using the maqasid al-shariah approach. The study employs a library research method by reviewing books, scholarly articles, regulations, and relevant policy documents. The data were analyzed descriptively and analytically using both conceptual and statutory approaches. The findings indicate that Green Waqf integrated with Smart Agriculture can serve as an innovative model for developing productive waqf through the utilization of technological assets, including agricultural drones, the Internet of Things (IoT), and digital agricultural platforms. This model is consistent with the objectives of maqasid al-shariah, particularly hifz al-mal (protection of wealth), hifz al-nafs(protection of life), hifz al-'aql (protection of intellect), and hifz al-bi'ah (protection of the environment). Accordingly, it provides a sustainable, inclusive, and technology-oriented framework for advancing agricultural modernization while promoting social welfare and environmental sustainability.